2022
DOI: 10.3390/jcm11113154
|View full text |Cite
|
Sign up to set email alerts
|

Development of Histologically Verified Thyroid Diseases in Women Operated for Breast Cancer: A Review of the Literature and a Case Series

Abstract: Background: The possible relationships between breast and thyroid diseases have been reported in the literature. The purpose of our study was to evaluate the occurrence of histologically verified thyroid pathologies in women who were diagnosed with breast cancer and, after mastectomy/quadrantectomy complemented by oncological treatment, were thyroidectomized based on their periodic thyroid evaluation. Patients and Methods: Our series consist of 31 women with a mean age of 62.9 ± 10.9 years (range, 45–81) treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Table 1 shown descriptive statistics of study parameters. 15 Hormonal factors may be associated with breast and thyroid diseases, as both organs are hormone-responsive and share similar hormonal pathways. For example, estrogen and progesterone receptors are present in both breast and thyroid tissues, and thyroid hormones modulate the estrogen receptors' expression in breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 shown descriptive statistics of study parameters. 15 Hormonal factors may be associated with breast and thyroid diseases, as both organs are hormone-responsive and share similar hormonal pathways. For example, estrogen and progesterone receptors are present in both breast and thyroid tissues, and thyroid hormones modulate the estrogen receptors' expression in breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…18 Additionally, some studies have suggested that hypothyroidism might be related to breast cancer in postmenopausal women. 15 Autoimmunity and functional immune system alterations have also been proposed as predisposing factors for the association between thyroid and breast disorders. 13 Several studies have worked on the association between thyroid and breast disorders, with varying results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, BC and differentiated thyroid cancer (DTC) are the most common malignancies among women and endocrine cancers, respectively, and their simultaneous presentation in the same patient should raise the suspicion of synchronous primary cancers, especially in light of the shared risk factors for these two types of tumors. [ 14 , 15 , 16 ]. Rare cases of TM from BC within another primary malignant thyroid cancer (“tumor-to-tumor metastasis”) have also been reported [ 17 , 18 ].…”
Section: Current Knowledgementioning
confidence: 99%